Long-term exposure to stress hormones induces malignant phenotype in oral keratinocytes - Cardoso, Diovana de Melo [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Abstract suprimido por orientação da Autora / Orientador
Long-term exposure to stress hormones induces malignant phenotype in oral keratinocytes
Keywords: Stress (Psicologia); Câncer; Boca Tumores; Carcinoma de células escamosas; Nitrosaminas; Catecolaminas; Norepinefrina; Adrenalina; Receptores adrenérgicos beta; Receptors, Adrenergic, beta